Bollywood Adaptations of Tess of the d'Urbervilles. Issue 3 (March 2016) - Dutta, Shanta
Abstract: The cinematic potential of Thomas Hardy's novels has long been recognized. Indeed, quite a few of his novels open with the reader/viewer getting a glimpse of a panoramic sweep of the English countryside, often with a solitary human figure silhouetted against a winding country lane. Focusing on two Hindi films, this essay considers ways in which Bollywood, the Hindi language film industry, has responded to Tess of the d'Urbervilles by adapting it to the Indian sociocultural milieu.